Linguistic and communicative performance in population with Fetal Alcohol Spectrum Disorders. Case Study - Vega-Rodríguez, Yuri E.; Garayzabal-Heinze, Elena; Moraleda-Sepúlveda, Esther (Revista de Investigación en Logopedia, 2024)
Fetal Alcohol Spectrum Disorders (FASD) are a set of clinical manifestations that include growth, physical, behavioral and cognitive deficits that have an impact on the development of language, speech and communication. The present study aims to examine the language and communication characteristics of 19 cases of individuals with FASD aged 6 to 17 years. The PEABODY and CELF-5 tests were used.  The results of the PEABODY test showed a group score of VIQ=71, which is considered moderately low. For the CELF-5 test, all indices were below average in all language skills assessed in the test. The population with FASD presents a profile of linguistic and communicative impairments that affect their performance in different developmental contexts. The limitations in these skills have a significant impact on the way they perform in social interactions and in their daily lives.
Keywords: Fetal Alcohol Spectrum Disorders; Language; Communication; Case study; Memory